O‘ZBEK VA QORAQALPOQ XALQ MAQOLLARINING BA’ZI LINGVOMADANIY XUSUSIYATLARI - Matjanov, Sh.A. (SCIENCE and SOCIETY, 2025)
In this article, the emergence of proverbs related to folklore in Uzbek and Karakalpak languages was analyzed in connection with traditions or traditions, as well as the linguistic and cultural characteristics of some proverbs.
Keywords: proverb; folk; language; manners; tradition; collection; folklorist; culturalist; genre; rhyme; idea